Aspectos morfológicos, citoquímicos e imunológicos da leucemia mielóide aguda no estado do Amazonas: estudo observacional em pacientes atendidos na Fundação de Hematologia e Hemoterapia do Amazonas - FHEMOAM - Alves, Eliana Brasil [UNIFESP] (2006)
Objective: The present study investigated the best laboratorial diagnosis methods to acute myeloid leukemia, acute undifferentiated leukemia and biphenotypic acute leukemia. We have prospective, observacional and descriptive study about 62 patients from Fundação de Hematologia e Hemoterapia do Amazonas - FHEMOAM, in the period of September of 2000 at June of 2003. The frequency, clinical and laboratories characteristics was analyzed. .Methods: The classification of the acute myeloid leukemia – LMA was stablished by morphological and cytochemical criteria according by the French-American-British (FAB) classification and immunologic aspects using the imunoenzymatic technique from DAKO - EnVision System Alkaline Phosphatase, that allows to identify to leukemia subgroups in bone marrow smears and/or peripheral blood and in cytospins, with a large monoclonal antibody panel. The LMA subtypes had been analyzed according age (children and adults), sex, morphologic and cytochemistry characteristics, immunophenotipic profile, lymph node and a variety of organs masses occurrence (lymph node ≥ 2 cm, spleen and liver ≥ 3 cm), laboratories findings as leucocytes and platelets counts, hemoglobin, countings. Results: We observed that the LMA occurred in 62 patients, being 25 children (40,3%) and 37 adults (60%); with predominance of the masculine sex happening in 66% of the cases (41 patients). The most common subtypes had been the LMA M2 in children and LMA M5, in adults; the phenotype more common had been CD13, CD33 and anti – MPO myeloid antigens. Auer’rod occurred in 26 cases (42%) and the more frequent laboratories findings had been leucocyte and platelets accounts below of 100.000/mm3 and hemoglobin below of 10g/dl. Limph node with more than 2 cm of diameter, spleen and liver with size bigger than 3 cm was observed in less than half of cases. The LAI was observed in 3 patients and the LAB in only 1 patient. Conclusion: The results indicate that FAB classification was very important at LMA diagnostic, however immunophenotyping has a strong importance in the M0 and M7 subtype of LMA classification, as well as in the characterization of the undifferentiated and biphenotypic acute leukemia. In this work, we observed some differences between data of the northeast region and Southeastern of Brazil as the frequency of the LMA M3 lower between our patients. In order hand, in our region we observed that LMA occurs in more young patients in relation to described in literature about other countries